A New Approach of the Tsunami Mitigation Strategies for the City of Banda Aceh, Indonesia - Halis Agussaini; Sirojuzilam Sirojuzilam; Rujiman Rujiman; Agus Purwoko (Indonesian Journal of Geography, 2022)
Ten years after rehabilitating and reconstructing some coastal areas of Banda Ache struck by the tsunami, and the city is currently repopulated, with most of its open land and community ponds converted into settlements. This rise in population needs to be controlled to minimize damages and casualties, assuming the tsunami hits again. Presently, the Banda Aceh City spatial plan for 2029 does not have a clear concept of tsunami mitigation, specifically in the spatial pattern of coastal areas. Therefore, this research aims to remap the vulnerability level of the Banda Aceh City coastal area from the tsunami hazard and determine alternative strategies based on the tsunami level in achieving safe, comfortable, productive, and sustainable spatial planning goals. This starts by analyzing the wave height generated by the earthquake that triggered this natural disaster and mapping the spatial distribution of the area and the tsunami's inundation height. The results showed that the proportionate regions prone to Level-2 tsunami were worse than the 2004 disaster based on the water level markers built in the city. The spatial planning strategies for the coastal area of Banda Aceh City are carried out by determining the level of tsunami-prone and the potential of the area's resources through a new approach of the multi-layer tsunami defence systems by combining sea dike, greenbelt, silvo-fishery, and the elevated road.